The Assesment of Demographic Characteristics Familial Variable and Mental Disorders in Child and Adolescent Sexual Abuse Cases - Demirci, Esra Özdemir; Özmen, Sevgi; Öztop, Didem Behice; Özdemir, Çağlar; Uytun, Merve Çıkılı (The Bulletin of Legal Medicine, 2014)
Sexual abuse is a major public health problem. With each passing day, the number of abuse cases is also increasing as well as the number of studies on sexual abuse. The aim is determine the sociodemographic characteristics and mental disorders of children reported with sexual abuse. The researchers have retrospectively examined the data of the children and the adults aged between 2 to 18, who suffered from sexual abuse and were referred to the Department of Child and Adolescent Psychiatry of Erciyes between January - July 2014. Frequency of abuse and for the mental disorders determined retrospective by DSM-TV-TR. Cases were composed of 54 girls and 6 boys. Mean age is 14.01 ± 2.37 in girls, 9.66 ± 3.07 in boys. Vaginal penetration is the most reported type of the sexual abuse in girls, anal penetration is the most reported type of the sexual abuse in boys. According to the psychiatric evaluation children; girls have acute stress reaction, boys have adjustment disorder. Sexual abuse; disrupt emotional, sexual, social development and have led to psychopathology. In studies, psychopathology, divorce and abuse history in parents of children is identified as a risk factor for abuse; which we were detected too. In accordance with the literature in the majority of cases are diagnosed in mental disorders Sexual abuse is a major public health problem, which increases risks for psychopathology development, so it is important to define demographic features. Key words: Children, Adolescents, Sexual abuse, Socio-demographic characteristics. Keywords: Children, Adolescents, Sexual abuse, Socio-demographic characteristics.